Early Cardiac Tamponade in a Patient with Postsurgical Hypothyroidism - Archana Sinha; Sri Lakshmi Hyndavi Yeruva; Rajan Kumar; Bryan H. Curry (Case Reports in Cardiology)
Pericardial effusion is a common cardiac manifestation of hypothyroidism, but effusion resulting in cardiac tamponade is extremely rare. We present a case of a 56-year-old African American woman with slurred speech and altered mental status that was initially suspected to have stroke. Her chest X-ray revealed cardiomegaly and subsequent echocardiogram showed a large pericardial effusion with echocardiographic evidence of cardiac tamponade. Clinically, patient did not have pulsus paradoxus or hypotension. Further questioning revealed a history of total surgical thyroidectomy and noncompliance with thyroid replacement therapy. Pericardiocentesis was performed promptly and thyroxine replacement therapy was started. Thereafter, her mental status improved significantly. The management of pericardial effusion associated with hypothyroidism varies depending on size of effusion and hemodynamic stability of the patient. The management strategy ranges from conservative management with close monitoring and thyroxine replacement to pericardiocentesis or creation of a pericardial window.